Pelatihan Content Creator Berbasis Jurnalisme Profetik Untuk Meningkatkan Kesadaran dan Partisipasi Sosial Pemuda di Desa Pepedan, Tonjong, Brebes - Aan Herdiana; Agung Triyatno; Nasya Puspa Angely; M. Zaldi Alfarizy (KREATIF: Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2025)
This community service project aims to enhance digital literacy, content creation skills, and the social awareness and participation of youth in Pepedan Village, Tonjong District, Brebes Regency, through a prophetic journalism-based content creator training program. The partner’s main problems include the low ability of local youth to use digital media productively and ethically, as well as the lack of collaborative spaces to express positive ideas through creative content. The program was implemented through three main stages: (1) improving digital literacy through outreach and interactive discussions; (2) technical training on creating creative content based on prophetic journalism values; and (3) mentoring for the establishment of a village content creator community. The results showed a significant improvement in participants’ ability to plan, produce, and distribute educational and socio-religious content. Moreover, the establishment of the Pepedan Village Content Creator Community has become a sustainable collaborative platform for youth empowerment in digital media and prophetic communication. Keywords: digital literacy, prophetic journalism, *content creator*, social participation, village youth